Manuel Fernández Acevedo (Madrid, 1744-1800): un pintor desconocido al servicio de Carlos IV - Gutiérrez Pastor, Ismael (Anuario del Departamento de Historia y Teoría del Arte, 1998)
In the next pages, I will try to reconstruct through some documents and a few signed works the artistically personality of Manuel Femández Acevedo (1744-1800), painter in the service of Carlos IV in the country houses of El Escorial, el Pardo and Aranjuez, as well as in the palaces of Madrid, La Granja de San Ildefonso and San Lorenzo de El Escorial. His figure fell into oblivion under the prominence of his contemporaneous, especially that of Vicente Gómez. The organisation of a provisional catalogue of his work, help us to emphasise his Academic Style and Rococo Aesthetic in an eminently devote and religious painting. On the other hand, Femández de Acevedo invested in commissioned works to satisfy the taste of King Carlos IV, both as Prince of Asturias and during his reign.